ANALISIS OPTIMALISASI PORTOFOLIO KREDIT USAHA KECIL DAN MIKRO Studi Kasus PT Bank Negara Indonesia (Persero) Tbk. Sentra Kredit Kecil Jakarta Kotapada Tahun 2009-2012 - , Indarto Purnomo, ST.; , Dr. Erni Ekawati, M.B.A. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This paper aims to analyze expansion of small and micro credit products that contribute to the optimal revenue in the BNI Sentra Kredit Kecil (SKC) Jakarta Kota to consider bad credit risk that may arise accompany the realization of credit dan loan portfolio expansion decision sensitivity to changes in interest rate. The Methods used in this study is a Linear Programming as a tool of decision making to optimize revenue. The methods for analyzing the credit quality is to analyze the data for all historical loan portfolio is in BNI SKC Jakarta Kota during the period from 2009 to March 2012. The calculation of Linear Programming and historical data analysis collectibility of loan products at BNI SKC Jakarta Kota regarding the collectibility of loan product is best Kredit Kepada Lembaga Keuangan (KKLK). Credit products BWU, KKLK and KUR of the calculation Linear Programming is a loan product that contributes to the optimal revenue, and from data analysis product collectibility KKLK has NPL value 0%, BWU has NPL value 3,71%, KUR has NPL value 7,81%. Based on historical data that KUR credit product riskier than KKLK and BWU so that the marketing of the product KUR have to be more carefully. Sensitivity BWU and KUR need to get attention because the value of the limit permitted changes is quite small only 0,57%, making it sensitive to changes in lending rates. See the trend rate of micro and small loans in BNI in 2010-2012, the estimated rate in 2013 was still stable, so the sensitivity of changes in interest rates on the product KUR dan BWU can still be anticipated and the results of this research can be implemented in BNI SKC Jakarta Kota.